German S1 guideline: Contact dermatitis. (8th May 2022) - Dickel, Heinrich; Bauer, Andrea; Brehler, Randolf; Mahler, Vera; Merk, Hans F.; Neustädter, Irena; Strömer, Klaus; Werfel, Thomas; Worm, Margitta; Geier, Johannes
Summary: Contact dermatitis is an inflammation of the epidermis and dermis at the site of exposure triggered by external agents. The two main forms are irritant and allergic contact dermatitis, which cause significant health and socioeconomic costs in addition to a marked reduction in quality of life. The anamnesis and the clinical picture are decisive for the necessary diagnostic measures. The most accurate possible diagnostic classification of contact dermatitis by means of allergological testing is important for disease management, since not only classical eczema therapy but also avoidance of the exogenous triggering factors are of great importance here. The choice of therapy should be based on the acuity, clinical severity, morphology of the lesions and localization of the contact dermatitis. A combination of basic therapy, topical, physical, and systemic therapy adapted to the patient's needs is required, whereby not all forms of therapy must be carried out simultaneously but can be used in a varying manner. Primary, secondary, and tertiary prevention strategies aim at the recognition of the triggering noxae or allergens with subsequent contact avoidance or minimization. The present S1‐guideline on contact dermatitis is primarily intended to provide dermatologists, allergologists and physicians working in allergology and occupational dermatology with a decision‐making aid for the selection and implementation of suitable and sufficient diagnostics, therapy, and prevention.